Development of E-Millenial Entrepreneur Learning Model for Entrepreneurs Learning of Vocational School - Nurjamiah, Nurjamiah; Sumarno, Sumarno; Gimin, Gimin (FKIP - Universitas Riau, 2020)
This study aims to develop an entrepreneurial learning model that can achieve the competencies expected at SMK Negeri 4 Pekanbaru. This research is a Research and Development using the Four D model. The Define phase deals with needs analysis which results in that teachers and students need a learning model that can help students to increase creativity in creating a product. The Design Phase is in the form of developing an initial learning model. The Development Stage is a learning model that has passed the validation test. Disseminate stage is the application of the model carried out in 6 (six) expertise programs in SMK 4 Pekanbaru. The results of the development in the form of learning activities given by the teacher to students to think about the types of products to be made, then students make the initial design for these products. After that students think about the materials needed, students calculate the funds needed, students determine the selling price for each product produced and the product can be promoted through the blog production unit of SMK Negeri 4 Pekanbaru. The results of the implementation carried out in 6 (six) skills programs show that the development of learning models named E-Millennial Entrepreneur Learning can improve the cognitive, affective, and psychomotor aspects of students.